The nutritional composition of Australian native grains used by First Nations people and their re-emergence for human health and sustainable food systems - Birch, Jacob; Benkendorff, Kirsten; Liu, Lei; Luke, Hanabeth (Frontiers in Sustainable Food Systems, 2023)
First Nations people of Australia sustained complex grassland grain production systems prior to colonisation. The revival of these foodways could aid in mitigating the interlinked issues of land degradation, reduced landscape resilience and declining food security. For the Gamilaraay people, efforts are underway to bring their ancient food system into a modern context with authenticity and integrity. The aim of this transdisciplinary study was to investigate the nutritional quality of Australian native grains to identify functional properties that may help promote this nascent industry; complimented by using autoethnography to understand how the original custodians, like the Gamilaraay people, might equitably benefit. Ethnographic findings highlight that Gamilaraay people aspire to improve their health and wellbeing through economic development and consumption of native grains, particularly Elders who disproportionately suffer from non-communicable disease. However, many First Nations people have lived experiences of being systemically exploited and excluded, particularly in the food and agriculture space. To prioritise the interests of the Traditional Custodians, the species used in the biochemical assays were de-identified. Wholegrains from seven culturally significant species, with domesticated brown rice as control, were analysed in triplicate for proximate, elemental, non-starch fatty acids, and total free phenolic content. Compared to brown rice, protein was significantly higher in all native species (9.4 – 32.6 g/100 g); whilst carbohydrates were significantly lower (36.5 – 53.7 g/100 g). One of the native species had exceptionally high total phenolics (569 mg GAE/100 g) compared to brown rice (60 mg GAE/100 g). All native species had generally higher elemental content, with significantly higher levels of Ca, Fe, Zn, Cu, Mg, P and K in two native species. All samples were dominated by unsaturated fats with significantly higher polyunsaturated fats in two native species. The generally low carbohydrates, high protein, good fats, high mineral content and high phenolic content suggests that native grains may be beneficial to human health by improving nutrient intake and protecting against non-communicable disease, thus marketable as functional foods. To ensure a flourishing industry where all of Australia benefits from these healthful grains, future research and industry development must be First Nations led.